Methacycline: A Review of Analytical Methods - da Silva, Lucclia M. [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Bentham Science Publ Ltd, 2012)
Methacycline is a broad spectrum, semisynthetic antibiotic prepared from oxytetracycline. Its antibacterial spectrum is as same as that of tetracycline, but its efficacy is superior to that of oxytetracycline and tetracycline. There is no standard technique for analysis and/or detection of methacycline. Practical requirements for high-sensitivity analysis and the need for a specialist laboratory setting create challenges for routine analysis. Several existing analytical techniques, which offer flexible and broad-based methods of analysis and detection, have been discussed in this manuscript, focusing on bioanalytical, pharmaceutical QC applications and food analysis. This review will examine the published analytical methods reported for determination of methacycline, presenting (a) sample pretreatment methods such as liquid-liquid extraction (LLE) and solid phase extraction (SPE), (b) separation methods such as thin layer chromatography, high performance liquid chromatography (HPLC) and capillary electrophoresis (CE) and (c) others such as potentiometry, spectrophotometry and microbiological assay, from which it can be seen that HPLC methods have been used most extensively.
Keywords: Analytical methods; Broad spectrum antibiotic; Methacycline; Tetracyclines